The Legacies of Vico: Philology, the Internet, the Posthuman - Timothy Brennan (Between, 2015)
Even in an era of the false populism of youth techno-cultures where intellectual dialogue seems dead on arrival, a political riposte of sorts is possible. It will find its resources in the apparently belated idea of "philology" – not understood as the old hoary science of the 19th century paleographic text, but a generalist, sociological quest for meanings as intentions. And in fact, philology has found a new popularity recently for just that reason. To speak of Vico at a conference of Italian comparatists may seem superfluous perhaps, and yet his contemporaneity in internet culture is not appreciated. Vico, not Spinoza, is the first Marxist before Marx; he anticipated anticolonial liberation theory, and he spoke directly to – while giving us weapons against – the posthumanism of internet culture.